PENGANGKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL DAERAH - Pramita, Dwi Kardri; Markeling, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
This paper is titled “THE APPOINTMENT OF VILLAGE’S SECRETARY INTO REGIONAL’SCIVIL SERVANT”. This paper used analytical normative method with the case approach and thefact approach. The interests regarding the governance affair will be handled by the governance’sservants or the civil servants, especially the village’s governance which is led by head man andthe village’s government staff. The Village’s Secretary is one of the village’s government staffwhich is a Regional’s Civil Servant. The Act Number 8 of 1974 on the Principals of Officialdomand its alteration the Act Number 43 of 1999 on the Alteration of the Act Number 8 of 1974 onthe Principals of Officialdom become the guidance on the appointment of Regional’s CivilServant, especially the explanation of the Article 16 paragraph 1 which is included in it. Theissues that writer raised are the procedures of appointing the Regional’s Civil Servant and theregulation of the Village’s Secretary into a Regional’s Civil Servant. The conclusion is theappointment of a Village’s Secretary into Regional’s Civil Servant can be done according to thesupporting criteria of national’s interest. The appointment of the village’s secretary intoRegional Civil Servant can be appointed directly without test, but should be fulfilling therequirement which has been determined because not all the village’s secretaries can be aRegional’s Civil Servant.
Keywords: Village’s Secretary, Civil Cervants, Appointment